Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.10.30.362582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of antibacterial compounds that block evolutionary pathways to resistance

Abstract: Antibiotic resistance is a worldwide challenge. A potential approach to block resistance is to simultaneously inhibit WT and known escape variants of the target bacterial protein. Here we applied an integrated computational and experimental approach to discover compounds that inhibit both WT and trimethoprim (TMP) resistant mutants of E. coli dihydrofolate reductase (DHFR). We identified a novel compound (CD15-3) that inhibits WT DHFR and its TMP resistant variants L28R, P21L and A26T with IC50 50-75 micromole… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 97 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…Of the assessed proteins besides folA (shown here for consistency on Fig. 6A and (Zhang et al, 2020)) only overexpression of folK showed clear sign of rescue from growth inhibition. folK encodes for 6-Hydroxymethyl-7,8-dihydropterin pyrophosphokinase (HPPK).…”
Section: Gene Overexpression Experiments Validate Functional Role Of Perturbed Metabolic Pathways In Cd15-3 Mechanism Of Actionmentioning
confidence: 58%
See 4 more Smart Citations
“…Of the assessed proteins besides folA (shown here for consistency on Fig. 6A and (Zhang et al, 2020)) only overexpression of folK showed clear sign of rescue from growth inhibition. folK encodes for 6-Hydroxymethyl-7,8-dihydropterin pyrophosphokinase (HPPK).…”
Section: Gene Overexpression Experiments Validate Functional Role Of Perturbed Metabolic Pathways In Cd15-3 Mechanism Of Actionmentioning
confidence: 58%
“…In the present study we deployed global metabolomics, gene over-expression, and growth recovery studies analysed in the context of the metabolic network to search for the cellular target of a novel "anti-evolution" lead CD15-3. We observed that CD15-3 markedly delays the emergence of antibiotic resistant bacterial phenotypes (Zhang et al, 2020). This could be attributed to factors like; 1) CD15-3 was designed to interact with WT as well as TMP resistant mutants which arise under conditions of TMP selection.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations